PENGARUH STRATEGI PAILKEM TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD MUHAMMADIYAH II PONTIANAK - Israyani, Nurul; Kartono, Kartono; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine wheather there is an effect or not and how much the effect has on PAILKEM strategy on student?s learning outcomes in Science for IV grade at Muhammadiyah II Elementary School Pontianak. The used method is an experiment in the form of quasi-experimental design with the kind of nonequivalent control group design. The population is all students of IV grade. The sample consisted of IV C grade as an experimental class and IV D grade as a control class selected by purposive sampling technique. Data collection technique that is used is measurement with data collection tool in written test in the form of multiple choices. Analysis of post-test results using the separated variance t-test shows the value of t_count (3,87) > t_table (1,99). It can be concluded that there is an effect of the PAILKEM Strategy on student?s learning outcomes. From the calculation of the effect size obtained 0,88 which means learning with PAILKEM strategy gives a large effect on student?s learning outcomes in Science for IV grade at Muhammadiyah II Elementary School Pontianak. Keywords: PAILKEM Strategy, Student?s Learning Outcomes